2006
DOI: 10.1111/j.1600-6143.2006.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated Posttransplant Lymphoproliferative Disorder of Donor Origin after Simultaneous Pancreas–Kidney Transplantation Limited to Pancreas Allograft: A Case Report

Abstract: A 45-year-old man was admitted with fever and elevated pancreas enzymes 6 months after simultaneous pancreas-kidney transplantation (SPKT). Function of the allografts was normal. Bacterial and fungal infections were excluded, while Epstein-Barr virus (EBV)-polymerase chain reaction (PCR) was positive. However, screening for EBV-associated lymphoma was negative. EBV infection did not respond to antiviral therapy. After an 18F-Fluorodeoxyglucose positron emission tomography positive signal and an abnormal comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We showed that the great majority of donor PTLDs arose in the graft itself (14/16). In the literature, 18 donor PTLDs were localized in or near the graft (10–31,42). Moreover, in these published reports of donor lymphomas, only one tumor was known to disseminate outside the graft (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the great majority of donor PTLDs arose in the graft itself (14/16). In the literature, 18 donor PTLDs were localized in or near the graft (10–31,42). Moreover, in these published reports of donor lymphomas, only one tumor was known to disseminate outside the graft (32).…”
Section: Discussionmentioning
confidence: 99%
“…From the histological point of view, a spectrum of lesions ranging from infectious mononucleosis to a malignant lymphoma comprises the clinical entity known as PTLD (9). A number of small‐scale studies and case reports have shown that PTLDs localized in the graft organ itself may originate from donor cells without being donor transmitted (10–31). Nevertheless, contrary to bone marrow transplant where PTLDs typically derive from donor lymphocytes, the majority of PTLDs that develop after organ transplantation derive from recipient lymphocytes (32–34).…”
Section: Introductionmentioning
confidence: 99%
“…Allograft involvement as a manifestation of plasmacytoma-like PTLD has been previously described in SOT, infiltrating liver [5, 12], kidney [13], and heart [14] transplants. Pancreas graft infiltration by an EBV-positive B-cell lymphoma was described by Rehbinder et al [15]. To our knowledge, this is the first report of an isolated pancreas allograft plasmacytoma-like PTLD.…”
Section: Discussionmentioning
confidence: 54%
“…As demonstrated across other solid organ transplants, disseminated disease carries a poorer prognosis than lymph node disease alone (3). Two case studies reported PTLD limited to the pancreatic allograft after SPK transplant (9,10). In each case, the recipient had multiple admissions and a presentation that was initially thought to be graft pancreatitis.…”
Section: Discussionmentioning
confidence: 99%